Developing indicators for Monitoring and evaluation of the implementation of the Primary Health Care Approach in Health Sciences at the University of Cape Town using a DELPHI method - Datay, Mohammed Ishaaq (Department of Medicine, 2021)
Background The University of Cape Town Faculty of Health Sciences (UCT FHS) adopted the Primary Health Care (PHC) approach as its lead theme for teaching, research, and clinical service in1994 Aim To develop indicators to monitor and evaluate the implementation of the PHC approach in Health Sciences Education . Method A Delphi study, conducted over two rounds, presented indicators of Social Accountability from the Training for Health Equity Network (THEnet), as well as indicators derived from the principles of the PHC approach in the UCT FHS, to a national multidisciplinary panel. An electronic questionnaire was used to score each indicator according to relevance, feasibility/measurability, and its application to undergraduate and postgraduate curricula. Qualitative feedback on the proposed indicators was also elicited. Results Round 1: Of the 59 Social Accountability indicators presented to the panel, the 20 highest ranked indicators were selected for Round 2. Qualitative feedback challenged the link between social accountability and PHC, resulting in an additional 19 PHC-specific indicators being presented in Round 2. Round 2: The indicators which scored >85% and made the final list were: PHC: Continuity of care (94%); Holistic understanding of health care (88%); Respecting human rights (88%); Providing accessible care to all (88%); and Promoting health through health education (88%). THEnet: Safety of learners (88%); Education reflects communities' needs (86%); Teaching embodies social accountability (86%); Teaching is appropriate to learners' needs (86%) Conclusion These PHC and THEnet indicators can be used to assess the implementation of PHC in Health Sciences Education. The specific indicators identified reflect priorities relevant to the local context. One limitation is that some key priority indicators did not make the final list.